1992
DOI: 10.1159/000200990
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Serotonin on the Immunoreactive Thyrotropin-Releasing Hormone Concentrations of the Rat Stomach

Abstract: The effects of serotonin and its related compounds on immunoreactive thyrotropin-releasing hormone (ir-TRH) concentrations of the rat stomach wall and gastric juice were studied. Either serotonin, cyproheptadine or GR38032F was injected intraperitoneally, and the rats were decapitated at various times after the injection. ir-TRH concentrations of the stomach wall and gastric juice were measured by radioimmunoassay, and gastric serotonin concentrations were measured by HPLC. ir-TRH concentrations of the stomach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Although intracisternal injection of TRH has been shown to exert the dual central effects of gastric cytoprotection and lesion formation on the basis of the balance between cytoprotective mechanisms and ulcerogenic factors (11), the relevance of TRH located peripherally in the stomach is poorly understood. Our recent studies showed that TRH was released from the gastric wall into the gastric juice in stress-(water immersion and cold restraint) or chemically induced experimental models of gastric mucosal lesions of the rat (6)(7)(8)(9)12). Under such experimental conditions TRH seemed to have ulcerogenic effects on the stomach by stimulating acid secretion in a paracrine manner.…”
mentioning
confidence: 99%
“…Although intracisternal injection of TRH has been shown to exert the dual central effects of gastric cytoprotection and lesion formation on the basis of the balance between cytoprotective mechanisms and ulcerogenic factors (11), the relevance of TRH located peripherally in the stomach is poorly understood. Our recent studies showed that TRH was released from the gastric wall into the gastric juice in stress-(water immersion and cold restraint) or chemically induced experimental models of gastric mucosal lesions of the rat (6)(7)(8)(9)12). Under such experimental conditions TRH seemed to have ulcerogenic effects on the stomach by stimulating acid secretion in a paracrine manner.…”
mentioning
confidence: 99%